Contemporary art in print : the publications of Charles Booth-Clibborn and his imprint the Paragon Press 1995-2000 - Booth-Clibborn, Charles; Elliott, Patrick; Lewison, Jeremy (Booth-Clibborn Editions, 2001)
"Since The Paragon Press was founded in 1986, it has established a reputation as one of the major print publishers of our time. Based in London, Paragon specialises in producing original print series by leading contemporary British artists, including Damien Hirst, Gary Hume, Anish Kapoor and Rachel Whiteread. This book illustrates and documents all twenty-five projects produced between 1995 and 2000, a period which has witnessed an extraordinary growth in interest in contemporary British art. Most of the series contain around 10 prints each, while some are much larger: the Chapmans' Disasters of War set comprises 83 separate etchings. Working in series, the artists have created narratives, or through repetition and emphasis have built a larger, grander statement than would be possible with single prints. In this way each project counts as an exhibition in itself, and most have taken months, if not years, to complete. The print techniques include screenprint, etching, linocut, woodcut and pigment prints." "The book contains a foreword by Charles Booth-Clibborn, founder of The Paragon Press, an introduction by Patrick Elliott, Assistant Keeper at the Scottish National Gallery of Modern Art in Edinburgh, and an essay by Jeremy Lewison, Keeper of Collections at the Tate, London. The print projects are illustrated in colour in chronological order and are followed by detailed narratives, mainly based on in-depth interviews, by Patrick Elliott. There are biographies and bibliographies of each artist. The book offers a thorough and indispensible survey of the many different trends in Contemporary British Art." --Book jacket.